Gaya Komunikasi Gibran Rakabuming Raka dalam Debat Cawapres 2024 Putaran Keempat pada Channel Youtube Kompas TV - Fascal Muhamad Akbari; Ratnaningrum Zusyana Dewi; Rahmad Saiful Ramadhani (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
The 2024 presidential and vice-presidential election also be an opportunity for the public to actively participate in the democratic process. One issue concerns the communication style of vice-presidential candidate Gibran Rakabuming Raka in the fourth round of the vice-presidential debate. The aim of this study is to identify the communication style demonstrated by Gibran Rakabuming Raka during the discussion. The data used for this research was taken from Kompas TV programs on the YouTube channel. The theoretical approaches used include Gibran’s Communication Style Theory and Carl Gustav Jung’s Communication Style Approach to better understand the characteristics and dynamics of communication. The research method employed is descriptive qualitative with content analysis, analyzing data from the discussion videos which serve as the main source of information. The results show that Gibran Rakabuming Raka's communication style in the fourth round of the vice-presidential debate reflects a unique blend of control style theory and social style theory elements.